Estimating total factor productivity in Vietnam’s agriculture: A non-parametric approach - Nguyen, Thanh Luan; Hoa, Ho Thi; Khanh, Vo Thi Van (Edelweiss Applied Science and Technology, 2025)
This study examines changes in agricultural Total Factor Productivity (TFP) and its components—Technical Efficiency Change, Technical Change, and Scale Change—in Vietnam over a 33-year period (1986–2018). Using a non-parametric Malmquist Data Envelopment Analysis (DEA) approach, the research analyzes a panel dataset comprising one aggregate output and five input factors across 60 provinces. The findings indicate a positive trend in agricultural TFP, with an average annual growth rate of 2% and a cumulative increase of 68% over the study period. Technological Change emerges as the primary driver of productivity gains, followed by improvements in Technical Efficiency. In contrast, Scale Change negatively affects overall TFP growth. The analysis reveals notable regional disparities: provinces in the Mekong River Delta and southern Vietnam demonstrate strong performance due to mechanization, high-value crop adoption, and better market integration, while provinces facing urbanization pressures or infrastructure constraints show slower, more erratic growth. These results underscore the importance of region-specific policy frameworks and targeted investment strategies to foster balanced and sustainable agricultural development nationwide.